Texting the future in Belgium and Québec: Present matters - Tremblay, Mireille; Blondeau, Hélène; Labeau, Emmanuelle (Journal of French language studies, 2020)
This study investigates the variation in the expression of Future Temporal Reference in text messages in Belgian and Québécois French. Three variants are considered: the Futurate Present, the Synthetic Future and the Analytic Future. The results of multivariate analyses show that the use of the Futurate Present does not appear to be subject to dialectal variation: both communities use this variant at similar rates, and the use of the variant is constrained by the same linguistic factors. The two dialects show differences in their choice of the Synthetic vs the Analytic Future. Unlike Québécois French, Belgian French strongly favours the Synthetic Future. The two dialects also differ with respect to the linguistic constraints in effect. Our analysis shows the need to explore the relationship between variants, and to distinguish between Covert T (realized as Present tense) and Overt T (either Synthetic or Analytic Future). Our results point toward the hybrid nature of text messages: while our results show patterns of use in line with oral/conversational corpora as reflected by the dialectal variation observed, text messages are not exempt from the influence of written French, as shown by the use of Synthetic Future forms in affirmative sentences in the Québec corpus.